Employee Competence And Performance In a Rattan Craft Enterprise: Evidence From Ud Meubel Sarira, Central Maluku - Zany Irayati Aunalal; Intan Toya; Evandro A.W Manuputty; Saul R.J. Saleky; Ashwin Siahainenia (Jurnal Administrasi Terapan, 2026)
Employee competence is crucial for labour intensive craft enterprises; yet evidence from micro-businesses in island regions remains limited. This study examines the effects of knowledge, skills, and attitudes on employee performance at UD Meubel Sarira, a rattan-furniture enterprise in Waitatiri, Central Maluku. A quantitative census design involved all 14 employees. Data were collected using a five-point Likert questionnaire, observation, and interviews, and were reanalyzed from respondent-level records using multiple linear regression. The measurement items were valid, while Cronbach's alpha ranged from 0.617 to 0.843. The regression model was significant (F = 8.216; p = 0.005) and explained 71.1% of performance variation. Skills had a positive and significant effect on performance (B = 1.072; p = 0.006), whereas knowledge (B = -0.172; p = 0.476) and attitudes (B = 0.011; p = 0.974) were not significant after controlling for the other predictors. The findings indicate that practical mastery especially equipment operation, product design, and task accuracy—is the most immediate competence lever in this craft-business setting. Due to the small, single-firm sample, the results should be interpreted as contextual evidence rather than broad population estimates. Keywords: employee competence; skills; attitude; employee performance; craft enterprise